The Effect Of Work From Home (Wfh) On Employee Performance At Agricultural Department Of Enrekang District - Irwan Abdullah; Muhammad Yusuf; Destri Kurniawan (Universitas Muhammadiyah Makassar, 2022)
This research is a research using quantitative methods with a sample size of 100 respondents. This study aims to determine the effect of work from home on employee performance at the Department of Agriculture of Enrekang Regency. Data obtained from the results of questionnaires distributed to respondents. The data analysis technique used validity test, reliability test, simple linear regression test, partial test (R2) and coefficient of determination test. The value of the coefficient of determination test (R2) is 0.313 so that it can be seen that the effect of work from home on employee performance is 9.8%. In the results of the t test, the variable coefficient value is 0.272 with a significant value of 0.002 (0.002 0.05), and the t arithmetic value is greater than t table (3.262 1.98). The results show that the hypothesis can be accepted because work from home has a positive and significant effect on employee performance